Short-term outcomes of faricimab and aflibercept 8 mg in diabetic macular edema - Carlo Maccauro; Yanny Jimenez Perez; Piergiorgio Neri; Ibraheem El Ghrably; Haytham I Salti; Francesco Pichi (AJO International)
Objective: To evaluate and compare the effectiveness and treatment burden of faricimab and aflibercept 8 mg in treatment-naive patients with diabetic macular edema (DME) using a pro re nata (PRN) protocol. Design: Retrospective, observational cohort study. Subjects: A total of 28 eyes from 18 treatment-naive patients diagnosed with DME were included. Fourteen eyes were treated with faricimab, and fourteen eyes were treated with aflibercept 8 mg. Patients were selected based on clinical and imaging criteria confirming the presence of center-involving DME requiring anti-vascular endothelial growth factor (VEGF) therapy. Methods: Patients received loading doses of either four monthly faricimab injections or three aflibercept 8 mg injections and were followed for a total of approximately 6 to 9 months, including both loading and PRN phases. Primary outcomes included changes in best-corrected visual acuity (BCVA) measured in logarithm of the minimum angle of resolution (logMAR), central retinal thickness (CRT) assessed via optical coherence tomography (OCT), and the number of injections required. Secondary outcomes included fluid resolution rates based on OCT findings. Statistical comparisons between groups were performed using independent two-sample t-tests, with a p-value <0.05 considered statistically significant. Main Outcome Measures: Changes in BCVA, CRT, injection frequency, and fluid resolution. Results: The mean BCVA change was -0.12 logMAR for faricimab and -0.10 logMAR for aflibercept 8 mg (p = 0.41). The reductions in CRT were 96.2 µm and 91.6 µm, respectively (p = 0.58). The injection burden was similar, with an average of 5.71 injections for faricimab and 5.14 for aflibercept 8 mg (p = 0.32). Fluid resolution rates did not differ significantly between groups. No serious adverse events were reported. Conclusions: Both faricimab and aflibercept 8 mg demonstrated significant improvements in BCVA and CRT. While the results suggest comparable efficacy and safety between the two treatments, this conclusion should be interpreted cautiously due to the study's limitations. Specifically, the relatively small sample size and short follow-up duration. These findings highlight the importance of individualized treatment considerations, such as cost, accessibility, and patient preference. Further prospective studies are needed to validate these results and assess long-term treatment durability across different regimens.